Development and Application of SSR Markers Related to Genes Involved in Leaf Adaxial-Abaxial Polarity Establishment in Chinese Cabbage (Brassica rapa L. ssp. pekinensis) - Gao, Ying; Lu, Yin; Li, Xiaoguang; Li, Na; Zhang, Xiaomeng; Su, Xiangjie; Feng, Daling; Liu, Mengyang; Xuan, Shuxin; Gu, Aixia; Wang, Yanhua; Chen, Xueping; et al. (Frontiers in Genetics, 2020)
In Chinese cabbage (Brassica rapa L. ssp. pekinensis), leaf adaxial-abaxial (ad-ab) polarity is tightly related to leaf incurvature, an essential factor for the formation of leafy heads. Therefore, identification of the genes responsible for leaf ad-ab polarity and studying their genetic variation may clarify the mechanism of leafy head formation. By comparing the sequences of the genes regulating leaf ad-ab polarity development in Arabidopsis thaliana (A. thaliana), 41 candidate genes distributed on 10 chromosomes were found to be responsible for the establishment of ad-ab polarity in Chinese cabbage. Orthologous genes, including 10 single copies, 14 double copies, and one triple copies, were detected in the Chinese cabbage. The gene structure and conserved domain analyses showed that the number of exons of the 41 candidate genes range from one to 25, and that most genes share the conserved motifs 1, 6, and 10. Based on the 41 candidate genes, 341 simple sequence repeats (SSRs) were detected, including five replicated types: single, double, triple, quintuple, and sextuple nucleotide replications. Among these sequence repeat (SSR) loci, 323 loci were used to design 969 specific primers, and 362 primer pairs were selected randomly and evaluated using 12 Chinese cabbage accessions with different heading types. 23 primer pairs resulting with clear, polymorphic bands, combined with other 127 markers, was used to construct a linkage map by using an F2 population containing 214 lines derived from the hybrid of the overlapping heading Chinese cabbage “14Q-141” and the outward curling heading Chinese cabbage “14Q-279”. The result showed that the sequences of markers in the genetic linkage map and the physical map was consistent in general. Our study could help to accelerate the breeding process of leafy head quality in Chinese cabbage.